DESIGN OF GEOMETRY OPTICAL TRAINERS FOR HIGH SCHOOL PHYSICS LEARNING (CONCEPTS OF HABITUATION, REFRACTIVE INDEX, CRITICAL ANGLE AND PERFECT REFLECTION) - Fatoni, Aisyah (Tesseract: International Journal of Geometry and Applied Mathematics, 2023)
This study aims to design and produce learning media in the form of geometric optical props that can show refraction events, critical angles and perfect reflection. This geometry optical instrument trainer can be used to calculate the magnitude of the refractive index between two mediums, while the mediums that can be used are liquid-air and liquid-liquid mediums. The method used in this study is the development research method, where the first step in this research is to conduct a needs analysis regarding the design of teaching aids to be made. This needs analysis involved 7 physics teachers and 111 grade XI science students from SMAN 3 Pandeglang, SMAN 3 Pandeglang and SMAN 10 Pandeglang. The results of this needs analysis obtained data that all students and teachers supported the design of this geometric optical trainer. Based on the needs analysis, then the design and manufacture of physics learning media in the form of geometry optical props were carried out followed by testing geometry optical props. This trial phase involved 7 expert lecturers, 11 physics teachers and 80 students of class XI high school science. The indicators measured in this study are design, concept suitability, content suitability and interactive. The design and testing stage of this teaching aid obtained a percentage achievement above 75%, meaning that the media is well designed. The results of this study generally show that geometric optical props can be accepted and used as a physics learning medium that can explain the concepts of refraction, refractive index, critical angle and perfect reflection